Analisa Perbandingan Algoritma Yamamoto’s Recursive Code Dan Algoritma Fibonacci Code Dalam Mengkompresi File Pptx - Rahadi Putra; Abdul Sani Sembiring; Saidi Ramadan Siregar (STMIK Budi Darma, 2022)
In the world of work, power point or pptx files are indispensable as presentation tools. By using pptx for presentations, presentation activities can be easier to explain. However, the problem that occurs is that sometimes the data size of this pptx file is quite large compared to other data, resulting in a waste of storage. So to solve the problem required compression technique, compression is to reduce the number of bits to be fewer, Thus, it is clear that the use of compression aims to reduce the percentage of storage. This research was conducted with the aim and purpose of analyzing the Yamamoto's recursive code algorithm and Fibonacci codes in pptx file compression with parameters, namely Ratio of Compression (RC), Compression Ratio (CR), and also Space Saving (SS). After being compressed then compare the performance of the two algorithms using the exponential method based on the parameter values that have been set. From the results of the study, the results obtained for the Yamamoto's recursive code algorithm with the RC value of 1.26, the CR value of 79.17%, and the SS value of 20.83%. For the results of the Fibonacci code algorithm, the RC value is 1.71, the CR value is 58.33%, the SS value and value is 41.66%. The results of the comparison of Yamammoto's recursive code algorithm and Fibonacci code obtained that the more optimal algorithm in compressing pptx files is the Fiboancci code algorithm with the acquisition of space saving values of 41.66%.